ON-LINE EDUCATIONAL ENVIRONMENT FOR SECONDARY SCHOOL TEACHERS - Svitlana G. Lytvynova (Інформаційні технології і засоби навчання, 2011)
In the article new approaches to formation of information-communication  educational environment for teachers are considered. Concept of On-line  interactive educational environment is analyzed, there are determined its characteristics,  stages of formation of On-line interactive educational environment are developed, it is proved its place in the system of distance learning as well as problems of its introduction into secondary education system are generalized. Considered training environment is directed on realization of aims and tasks in general educational establishments. Models of the organization of  educational process are generalized by means of On-line training.